Religious Learning at Material of Tolerance in the Salatiga State Vocational of High School (SMK) - Ahmad Fikri Sabiq; Abdul Ckamim (ISTAWA, 2020)
ABSTRACT: This research is motivated because of the importance of instilling tolerance values to students in the school environment, so students can become individuals who have an open mind, are not rigid, have a good characteristic, and accept a difference. This study aims to determine the content of tolerance values in the development of Islamic, Christian, and Buddhist religious education materials and to determine the efforts of Islamic, Christian, and Buddhist Religious Education teachers in instilling tolerance values to students in the Salatiga State Vocational of High School (SMK) Year 2019. This research method uses a qualitative approach by examining documents that are learning materials either from textbooks or materials from the Lesson Plan (RPP) made by teachers and interviews about teacher efforts in instilling tolerance values to students. The data obtained is then outlined in the form of a description, not in the form of numbers. Based on the results of a study of Islamic, Christian, and Buddhist religious education as a whole, it meets the principles of developing learning materials and contains tolerance values. Overall Islamic Religious Education (GPAI) teachers, Christian religious education teachers (GPAK), Buddhist religious education teachers (GPAB) have an effort to instill tolerance values to students who meet three aspects of their assessment, namely aspects of peace, aspects of respecting differences and aspects of awareness. From this study, it was concluded that the learning of Islam, Christianity, and Buddhism in the Salatiga State Vocational of High School (SMK) in 2019 was based on a review of the development of material from textbooks and materials from the Lesson Plan (RPP) and based on the efforts of teachers in carrying out learning in it there are tolerance values.    Penelitian ini dilatarbelakangi akan pentingnya penanaman nilai toleransi kepada siswa di lingkungan sekolah, agar siswa dapat menjadi pribadi yang memiliki fikiran terbuka, tidak kaku, berakhlak baik, dan dapat menerima sebuah perbedaan. Penelitian ini bertujuan untuk mengetahui muatan nilai toleransi pada pengembangan materi dan upaya guru dalam penanaman nilai-nilai toleransi kepada siswa pada mata pelajaran Pendidikan Agama Islam, Kristen, dan Budha di Sekolah Menengah Kejuruan (SMK) Negeri  Kota Salatiga Tahun 2019. Metode penelitian ini mengggunakan pendekatan kualitatif dengan menelaah dokumen materi pembelajaran dan wawancara kepada guru. Data yang diperoleh dituangkan dalam bentuk diskripsi. Berdasarkan hasil telaah materi Pendidikan Agama Islam, Kristen, dan Budha secara keseluruhan memenuhi prinsip pengembangan materi pembelajaran dan di dalamnya mengandung nilai toleransi. Secara keseluruhan guru Pendidikan Agama Islam, Guru pendidikan Agama Kristen, dan Guru Pendidikan Agama Budha memiliki upaya dalam menanamkan nilai toleransi kepada siswa yang memenuhi tiga aspek yaitu kedamaian, menghargai perbedaan dan aspek kesadaran. Dari penelitian ini didapatkan kesimpulan bahwa pembelajaran agama Islam, Kristen dan Budha di Sekolah Menengah Kejuruan (SMK) Negeri Kota Salatiga tahun 2019 berdasarkan telaah pengembangan materi dari buku paket dan materi dari Rencana Pelaksaan Pembelajaran (RPP) serta berdasarkan upaya guru dalam melaksanakan pembelajaran di dalamnya terdapat nilai-nilai toleransi.